Optimisation and characterisation of red palm carotene-based microcapsules stabilised by rice protein isolate-flaxseed gum complex using various coating materials and core-to-wall ratios - Choy, Hew Weng; Teow, Shuh June; Khor, Yih Phing; Tan, Tai Boon; Mat Yusoff, Masni; Gholivand, Somayeh; Tan, Chin Ping (Universiti Putra Malaysia, 2025)
The present work explores the impact of various wall materials and core-to-wall material ratios on carotene microcapsules’ physicochemical properties. Palm carotene-based microcapsules were prepared using spray drying with different wall materials (maltodextrin, starch sodium octenyl succinate (OSS), inulin) and core-to-wall ratios (1:2, 1:3, 1:4), followed by physicochemical characterisation including moisture content, water activity, microencapsulation efficiency, and morphological analysis via scanning electron microscope (SEM). Microcapsules created with a 1:4 core-to-wall material ratio, combining maltodextrin and OSS, exhibited optimal traits. These microcapsules possessed the lowest moisture content (2.19%) compared to 1:2 (2.73%), 1:3 (2.65%), and water activity (0.20 aw), maintaining adequate flowability and intermediate cohesiveness. The same sample demonstrated the highest MEE at 70.50%, compared to 1:2 (24.57%) and 1:3 (35.80%), corresponding to α-carotene (60.85%) and β-carotene (72.79%) content. SEM confirmed their smooth, undented surface, indicating successful encapsulation. Furthermore, microcapsules stabilised with this combination at a 1:4 ratio displayed a superior WSI of 79.59% and a lower WAI of 0.50%, enhancing storage stability and suitability for diverse food systems. The present work thus demonstrated the significance of wall materials and core-to-wall ratios in producing high-quality, functional carotene microcapsules.